The Impact of the Antitobacco Norm on the Selected Mode of Cognitive Dissonance Reduction. Issue 1 (20th December 2012) - Voisin, Dimitri; Stone, Jeff; Becker, Maja
<x xml:space="preserve">Abstract</x> Two experiments tested the hypothesis that when behavior violates an antismoking injunctive norm, dissonance is aroused, but the injunctive norm constrains how people reduce their discomfort. In Experiment 1, participants with positive or negative attitudes toward public smoking wrote an essay for or against a ban on public smoking. Whereas attitude change occurred for those whose counter‐attitudinal essay supported the antismoking norm, those whose counter‐attitudinal essay violated the antismoking norm did not change their attitudes to reduce dissonance. In Experiment 2, participants who wrote against the ban on public smoking eschewed attitude change in favor of reducing dissonance through trivialization and act rationalization. The discussion focuses on how maintaining social connections makes cognitions resistant to change when dissonance is aroused.